Marco Jurídico Referido a la Discapacidad: Especial Referencia a la e-Accesibilidad - Serrano Mascaraque , Esmeralda (Cuadernos de Documentación Multimedia, 2009)
Lists the main standards that affect the field of disability, from the standpoint of access to information through new technology, nationally and, more briefly, at the international level. Besides, it aims to outline the current situation of the tax measures of this group need the protection of the public authorities. The collection includes the most current rules, only those provisions that expressly refer to the subject and an instructive and educational interpretation of it.
Keywords: Web accessibility; e-accessibility; Information and Communication Technologies (ICT); Information Society; Disability; Legislation; Spain